Human Y‐chromosome SNP characterization by multiplex amplified product‐length polymorphism analysis. Issue 17 (14th July 2014) - Medina, Laura Smeldy Jurado; Muzzio, Marina; Schwab, Marisol; Costantino, María Leticia Bravi; Barreto, Guillermo; Bailliet, Graciela
<x xml:space="preserve">Abstract</x> We designed an allele‐specific amplification protocol to optimize Y‐chromosome SNP typing, which is an unavoidable step for defining the phylogenetic status of paternal lineages. It allows the simultaneous highly specific definition of up to six mutations in a single reaction by amplification fragment length polymorphism (AFLP) without the need of specialized equipment, at a considerably lower cost than that based on single‐base primer extension (SNaPshot™) technology or PCR‐RFLP systems, requiring as little as 0.5 ng DNA and compatible with the small fragments characteristic of low‐quality DNA. By designation of two primers recognizing the derived and ancestral state for each SNP, which can be differentiated by size by the addition of a noncomplementary nucleotide tail, we could define major Y clades E, F, K, R, Q, and subhaplogroups R1, R1a, R1b, R1b1b, R1b1c, J1, J2, G1, G2, I1, Q1a3, and Q1a3a1 through amplification fragments that ranged between 60 and 158bp.